Full Metal Jhacket - Derby, Matthew, 1973- (Book collections on Project MUSE., 2015)
Following his celebrated debut collection Super Flat Times, Matthew Derby delivers a disturbing new set of stories that plunges us into a lonely heartland of misfits, outcasts, and would-be assassins who lurk in the shadows, searching for connection and meaning in all the wrong places.